The cephalic vein is readily accessible for vascular access in pediatric patients less than 12 weeks presenting to an emergency room - Zilberfarb, Alexandra L.; Odunayo, Adesola; Garudadri, Prathima; Allen-Durrance, Ashley; Okafor, Chika (Frontiers in Veterinary Science, 2025)
Pediatric veterinary patients often require prompt medical intervention in emergency hospitals, commonly involving intravenous medications or fluids. This study aimed to characterize the most utilized venous access sites in pediatric puppies and kittens under 12 weeks of age in an emergency room setting. Ninety-four canine and 33 feline patients under 12 weeks old, with an intravenous catheter placed in the emergency room at the University of Florida, between January 1, 2021, and November 30, 2023 were included in this study. A retrospective evaluation of medical records was conducted to determine the most common vein utilized for venous access in pediatric patients. The median body weight was 4.19 kg (Q1, Q3: 2.50, 7.20) for puppies and 0.92 kgs (Q1, Q3: 0.43, 1.14) for kittens. The cephalic vein was the most common site in both species, utilized in 90.4% of puppies (85/94) and 78.8% of kittens (26/33). Puppies with lower body weights were more likely to have a catheter placed in the jugular vein; however, no significant correlation was found between the kittens’ body weights and catheter site. The most used catheter size was 22G in both species. Ultimately, the cephalic vein appears to be consistently accessible for venous access in puppies and kittens under 12 weeks old, across a wide range of body weights. Catheters in the jugular vein may be preferred for puppies and kittens under 1.2 kg and 0.3 kg, respectively. Utilizing the cephalic vein for venous access may facilitate rapid and less technically challenging intravenous catheter placement in patients under 12 weeks old.